EXPERIMENTAL STUDY OF TACTICAL AND TECHNICAL CHARACTERISTICS OF THE ELECTRIC DRIVE OF A STRIKEBALL WEAPON. - Berezhansky, O. A.; Markov, A.M. (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
Electro-pneumatic actuator is an accurate external modulation of combat weapons, which is used for tactical games and development of combat skills. Electro-pneumatic drive (AEG) and its advantage in high speed of fire were investigated in the experiment and the number of its shots exceeds even the number of combat weapon's shots. The other advantages are the large number of shots on a standard battery and miniature design, because weight and size are more modulation requirement than necessity.